Pengaruh Dukungan Selebriti, Ulasan Pelanggan, Dan Pemasaran Viral Pada Media Sosial Tiktok Terhadap Keputusan Pembelian Produk Somethinc Di Provinsi Lampung - Vinna Asadilla; Aripin Ahmad; Mudji Rachmat Ramelan (Shofanah Media Berkah, 2023)
The phenomenon of internet development today encourages every company to do online marketing through social media, one of which is TikTok. TikTok is a social media platform that presents videos, live streaming, and online shops. Somethinc as a beauty brand that sells various cosmetic and skincare products, uses TikTok as its marketing tool. This study aims to determine the influence of celebrity endorsements, customer reviews, and viral marketing on purchasing decisions. The population in this study is TikTok users in Lampung Province who have used Somethinc products.This research is categorized as field research where the research instrument is in the form of distributing questionnaires to respondents. The sample used was 130 respondents determined by purposive sampling technique. Data collection using questionnaires that have been tested for validity and reliability. The analysis in this study used multiple linear regression. The results of this study show that celebrity endorsements, customer reviews, and viral marketing have a significant effect on buying decisions.